Environment, Development and Security in Southeast Asia: Exploring the Linkages - Jennifer Clapp; Peter Dauvergne (Development and Security in Southeast Asia – Volume 1: The Environment, 2003)
Challenging the conventional wisdom about the beneficial results of economically induced change, this first volume suggests that too often the mismanagement of development jeopardises the security of individuals, families, communities, and possibly the state, by harming the very environment which is required to sustain both people and their economic existence. Bringing together an international group of scholars from a variety of disciplines, this volume is relevant for all those interested in Southeast Asia.